Relationship between distinctive face and typical face description, facial composite and face recognition accuracy - Vanagaitė, Kristina (Psichologija, 2006)
The article analyses the relationship between the accuracy of distinctive face or typical face description, similarity of facial composite and face recognition accuracy. The research pursued two goals: 1) determine the accuracy of describing the distinctive and typical male faces under examination (by using a cognitive or semi-standardized interview), the similarity of facial composites produced for target faces and the accuracy of recognizing the target face (when the recognition is carried out immediately after producing a facial composite or 30 minutes later); 2) determine the interval of time between the face memorization and face recognition and the influence of tasks performed during this interval to the accuracy of face recognition. The research involved 224 (112 male and 112 female) participants. At first the participants were shown coloured photos of typical or distinctive target male face on the computer screen to be memorized and recognized later (during the recognition the previously demonstrated face was shown among other 5 faces which had only one different feature). The control group participants (n = 96) had to recognize the target face after different time intervals (10, 60 and 90 min.) from memorization. The experimental group participants (n = 128) had to describe a face memorized at the beginning of the study, make his facial composite and recognize the target face (immediately after making the face composite or after a 30-minute break). Two experts assessed the accuracy of describing the target faces and the similarity of facial composites produced. The research results revealed that a combination of face description and facial composite production reduces the accuracy of face recognition if the face has to be recognized immediately after the production of facial composite. Meanwhile, at least a 30-minute break between producing a facial composite and recognizing the face significantly improves the accuracy of face recognition from the statistical point of view. Expert assessment results revealed very low similarity between the facial composites produced by the participants and the target faces. On the other hand, the experts found the descriptions of target faces given by the participants fairly accurate. The finding is that the more accurate description (recollecting more accurate and less subjective details) is related with higher similarity of produced facial composites. However, neither more accurate face description nor higher similarity of produced facial composite is related with the accuracy of target face recognition. Statistically, there were no significant differences between the recognition of a distinctive and a typical face. A relatively low difference in the accuracy of recognizing a distinctive and a typical face could result from attributing distinctiveness and typicality to certain features of the face. Besides, the research revealed a tendency that a typical target face, compared to a distinctive face, is not only described more accurately, but, in the opinion of experts, the produced facial composites of typical face have higher similarity to the target face.